Green Advertising, Eco Labels, Environmental Responsibility and Green Purchase Behavior: Environmental Attitude as mediation - Purwoko, Purwoko; Fikri, Muhammad Ali; Rini, Poppy Laksita; Marhadi, Marhadi (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study uses environmental attitude as a mediating factor to investigate how green advertising, eco labels, and environmental responsibility affect green purchase behavior. Design/Methodology/Approach: Data collection using the purposive sampling method, using 138 NPURE cosmetic consumers, with SmartPLS 4.0 statistics tool.Research findings: Green purchase behavior is not positively impacted by green advertising. Green purchase behavior is not positively impacted by eco labels. Green purchase behavior is positively impacted by environmental responsibility. Environmental attitudes are positively impacted by green advertising. Environmental attitudes are positively impacted by eco labels. Environmental attitude is positively impacted by environmental responsibility. Green purchase behavior is not positively impacted by environmental attitude. Additionally, it was discovered that the impact of green advertising on green purchase behavior was not mediated by environmental attitude. Green purchase behavior and eco labeling was not mediated by environmental attitude. Environmental responsibility and green purchase behavior was not mediated by environmental attitude.Theoretical Contribution/Originality: This study demonstrates a negative influence, underscoring the persistently high level of consumer skepticism, in contrast to other research that typically finds a positive association green advertising and green purchase behavior. The insignificant mediation role of environmental attitude provides a new perspective on how psychological factors and consumer behavior interact in the context of sustainability.Practitioners/Policy Implications: Companies need to adopt more transparent and credible communication strategies in implementing green advertising in order to overcome consumer skepticism.Research Limitations/Implications: This study used quantitative methods that may not capture the deeper psychological and emotional aspects related to green purchasing decisions. Therefore, future research should explore qualitative approaches to understand consumer motivations more deeply and integrate external factors that may influence green purchase behavior.